Keeping children healthy at summer camp: A study of medications administered in the camp setting. Issue 2 (3rd April 2023) - Funk, Tara; Quach, Leon; Mahajan, Aditi; Modi, Sarang; Supenia, Emily; Schellpfeffer, Natalie; Ambrose, Michael; Gaslin, Tracey; Garst, Barry; Hashikawa, Andrew
ABSTRACT: Summer campers often require access to medications. However, little is known about the types of medications administered in camps. We used a data set from a camp-specific electronic records system that contained all campers' medications. We developed a coding book and classified medications based on drug type, mechanism, and indication. Data were available on 163, 853 medications from 75, 072 campers. Health care providers need to be aware of the vast quantity and wide spectrum of medications dispensed in summer camps and should find opportunities to advocate for the adoption of best-practice safety guidelines to ensure the safety and well-being of campers.